Build your vocabulary 2 - Flower, John.; Berman, Michael (England : Language teaching Publications, 1989)
Every student knows how important it is to know enough words. Build your vocabulary is a series of lively graded practice books which help students to learn and use words more effectively.
Keywords: English language; Vocabulary; English language -- Vocabulary